A Model For Developing High-Performance Human Resources With A Team Coaching Approach (Case Study: Knowledge-Based Companies In The Science And Technology Parks Of Tehran) - Yousefi fard, Arsalan; Slambolchi, Alireza; Sarafrazi, Mehrzad; Hamidi, Kambiz; Nik Nafas, Javad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  This study aims to explore the key factors influencing high-performance human resource development through a team coaching approach.Methodology: A mixed-method approach was employed, including a review of relevant literature and empirical research, to identify the factors and strategies that contribute to high-performance human resource management through team coaching in organizational settings.Findings: The research identified several key factors impacting high-performance human resource development, including empowerment of human resources, organizational capabilities, contextual conditions, and intervention factors. Team coaching was found to significantly enhance decision-making, social responsibility, and human resource flexibility, ultimately contributing to higher organizational effectiveness. Additionally, factors such as leadership styles, team behaviors, and the acceptance of coaching practices were essential for successful implementation.Conclusion: The findings suggest that high-performance human resource management, facilitated by team coaching, is essential for organizational growth, productivity, and competitiveness. Organizations should foster an environment of learning, adaptability, and commitment to maximize the potential of their human capital through structured coaching interventions.